2019
DOI: 10.1111/cea.13406
|View full text |Cite
|
Sign up to set email alerts
|

The association of allergic sensitization patterns in early childhood with disease manifestations and immunological reactivity at 10 years of age

Abstract: Background: Allergy to German cockroach (CR) is common in urban environmentsand is an important allergen in children with asthma.Objective: We hypothesize that the evolution of allergic sensitization and clinical disease is associated with distinct patterns of allergen-specific T cell reactivity. To test this hypothesis, a subset of high-risk inner-city children participating in the URECA (Urban Environment and Childhood Asthma) birth cohort were selected to evaluate CR-specific T cell reactivity from three di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 25 publications
0
6
3
Order By: Relevance
“…In This study is to the best of our knowledge, the first characterization of ex vivo CR-specific CD4+ T cell responses in CR-sensitized urban and under-resourced children with asthma, and for the majority of the known CR allergens to date, which are also components commonly found in CR extracts used for IT. 2,10 Our results also differ from previous attempts of portrayal of CR-specific responses, 17,19,20 because of the high level of granularity and because the ex vivo sponses, namely to cat dander, fungus, mite and grass or birch pollen 30,46,47 using ex vivo methodologies similar to our study. It is possible that the ex vivo assay strategy utilized contributed to reveal this heterogeneity, as previous allergy studies in the case of CR 16,18,20 or other allergens 24,27 utilized in vitro restimulation protocols which might obscure and blunt differences.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In This study is to the best of our knowledge, the first characterization of ex vivo CR-specific CD4+ T cell responses in CR-sensitized urban and under-resourced children with asthma, and for the majority of the known CR allergens to date, which are also components commonly found in CR extracts used for IT. 2,10 Our results also differ from previous attempts of portrayal of CR-specific responses, 17,19,20 because of the high level of granularity and because the ex vivo sponses, namely to cat dander, fungus, mite and grass or birch pollen 30,46,47 using ex vivo methodologies similar to our study. It is possible that the ex vivo assay strategy utilized contributed to reveal this heterogeneity, as previous allergy studies in the case of CR 16,18,20 or other allergens 24,27 utilized in vitro restimulation protocols which might obscure and blunt differences.…”
Section: Discussioncontrasting
confidence: 99%
“…This study is to the best of our knowledge, the first characterization of ex vivo CR‐specific CD4+ T cell responses in CR‐sensitized urban and under‐resourced children with asthma, and for the majority of the known CR allergens to date, which are also components commonly found in CR extracts used for IT. 2 , 10 Our results also differ from previous attempts of portrayal of CR‐specific responses, 17 , 19 , 20 because of the high level of granularity and because the ex vivo approach allowed to characterize responding cells to a minimal gap from bona fide in vivo responses.…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…CR-specific T cell responses have been characterized in relatively low detail ( 5 7 , 47 ), and very little information is available particularly addressing if T cells play a role in cockroach allergic sensitization. Although it has been shown that higher T cell reactivity is associated with allergen sensitization and asthma ( 48 ), future studies are warranted to elucidate to which extent T cell responses correlate with clinical symptoms or disease severity. An important implication of the current study is that knowledge of individual reactivity profiles will help to interpret outcomes of cockroach immunotherapy, according to the allergens present in the cockroach extract used for treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In this issue of the Journal, Schulten et al assess whether the development of allergic sensitization and clinical disease is associated with specific patterns of allergen‐specific T cell reactivity towards German cockroach. They used a subgroup from the URECA (Urban Environment and Childhood Asthma) high‐risk birth cohort.…”
mentioning
confidence: 99%